Product TDS & test report & comparing of Vanlei inorganic concrete curing (RFA-361_Rev E) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.